Tertiary paediatric hospital health professionals' attitudes to lesbian, gay, bisexual and transgender parents seeking health care for their children. Issue 23 (December 2013) - Nicol, Pam; Chapman, Rose; Watkins, Rochelle; Young, Jeanine; Shields, Linda
Abstract : Aims and objectives: To ascertain health professionals' knowledge, attitudes and beliefs towards lesbian, gay, bisexual and transgender parents seeking health care for their children in a paediatric tertiary hospital setting which practises family‐centred care. Background: Lesbian, gay, bisexual and transgender parents are often reluctant to disclose their sexual orientation to health professionals for fear of discrimination and compromised quality of care. Staff knowledge, attitudes and beliefs can influence disclosure by parents, but little is known about knowledge, attitudes and beliefs in paediatric tertiary hospital staff towards lesbian, gay, bisexual and transgender parents accessing care for their children. Design: Descriptive comparative study of health staff using a cross‐sectional survey. Methods: A set of validated anonymous questionnaires was used to assess knowledge about homosexuality, attitudes towards lesbians and gay men, and gay affirmative practice. Three open‐ended questions were also used to assess beliefs about encouraging disclosure of lesbian, gay, bisexual and transgender parenting roles and how this may impact on care. Results: Of the 646 staff surveyed, 212 (32·8%) responded. Knowledge and attitudes were significantly associated with professional group, gender, Caucasian race, political voting behaviour, presence of religious beliefs, the frequency of attendance at religious services, the frequency of praying, and having a friend who was openly lesbian, gay, bisexual and transgender. Conclusion: This study highlighted that staff working in a tertiary paediatric hospital setting, with family‐centred care models in place, held attitudes and beliefs that may impact on the experience of hospitalisation for lesbian, gay, bisexual and transgender parents, and the quality of care received by their children. Relevance to clinical practice: To promote equitable care to all families, organisations should ensure that family‐centred care policies and guidelines are adopted and appropriately implemented. In addition to formal education, affirmative health service action and innovative methods may be required.